NLRP3 Inflammasome Activation Enhanced by TRIM25 is Targeted by the NS1 Protein of 2009 Pandemic Influenza A Virus - Park, Hong-Su; Lu, Yao; Pandey, Kannupriya; Liu, GuanQun; Zhou, Yan (Frontiers in Microbiology, 2021)
Nucleotide-binding domain and leucine-rich repeat-containing protein 3 (NLRP3) inflammasome-mediated interleukin-1 beta (IL-1β) production is one of the crucial responses in innate immunity upon infection with viruses including influenza A virus (IAV) and is modulated by both viral and host cellular proteins. Among host proteins involved, we identified tripartite motif-containing protein 25 (TRIM25) as a positive regulator of porcine NLRP3 inflammasome-mediated IL-1β production. TRIM25 achieved this function by enhancing the expression of pro-caspase-1 and its interaction with apoptosis-associated speck-like protein containing caspase recruitment domain (ASC). The N-terminal RING domain, particularly residues predicted to be critical for the E3 ligase activity of TRIM25, was responsible for this enhancement. However, NS1 C-terminus of 2009 pandemic IAV interfered with this action by interacting with TRIM25, leading to diminished association between pro-caspase-1 and ASC. These findings demonstrate a novel role of TRIM25 to promote IL-1β production, while it is repressed by IAV NS1 protein through additional antagonism against host pro-inflammatory responses.